The terror of Tiny Town - Newfield, Sam, 1899-1964; Myton, Fred, 1885-1955; Curtis, Billy, 1909-1988; Moray, Yvonne; Columbia Pictures Corporation; Principal Productions, Inc.; Cinetel Films ([Los Angeles, CA] : Principal Productions, Inc., 1938)
An evil gunslinging midget comes to terrorize the good little people of Tiny Town. The townspeople organize to defeat him, and zany antics ensue, --
Originally released as a motion picture in 1938.
Billy Curtis, Yvonne Moray, Little Billy, Billy Platt, John Bambury, Joseph Herbst.
Cinematographer, Mack Stengler; editor, Martin G. Cohn and Richard G. Wray; songs by Lew Porter; musical background by Edward Kilenyi.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Dwarfs -- Drama; West (U.S.) -- Drama; Western films; Comedy films; Musical films; Feature films; Internet videos; Streaming video